The Effect of the Brexit Vote on the Variation in Race and Religious Hate Crimes in England, Wales, Scotland and Northern Ireland - Williams, Matthew (The British journal of criminology, 2023)
This paper examines possible mechanisms behind the spike in racially or religiously-aggravated (RR) offences after the Brexit vote. It adds to the current literature in five significant ways: (1) it provides the first Brexit-related RR hate crime comparison between England and Wales, Scotland and Northern Ireland; (2) it reports on results from a national-level panel model that adds to the debate in the literature on whether pro-leave or pro-remain areas saw greater increases hate crimes; (3) it assesses the role of demographic characterises on the variation in hate crime; (4) it compares the effect of the vote with other ‘trigger events’; and (5) it uses social media data to control for variation in hate crime victim and witness reporting.